A survey on power management strategies of hybrid energy systems in microgrid - G. R. Prudhvi Kumar; D. Sattianadan; K. Vijayakumar (Institute of Advanced Engineering and Science, 2020)
The power generation through renewable energy resources is increasing vastly, Solar energy and Wind Energy are the most abundantly available renewable energy resources. The growth of small scale distributed grid networks increasing rapidly in the modern power systems and Distributed Generation (DG) plays a predominant role. Microgrid is one among the emerging techniques in power systems. Power Management is mainly required to have control over the real and reactive power of individual DG and for smooth operation, maintaining stability and reliability. This paper presents a survey of the research works already reported focusing on power management of hybrid energy systems such as mainly solar and wind systems in microgrid. Six different approaches have been studied in detail for AC,DC and hybrid AC/DC microgrid.